Agonists with supraphysiological efficacy at the muscarinic M2 ACh receptor. (25th April 2013) - Schrage, R; Seemann, WK; Klöckner, J; Dallanoce, C; Racké, K; Kostenis, E; De Amici, M; Holzgrabe, U; Mohr, K
<x xml:space="preserve">Abstract</x> Background and Purpose Artificial agonists may have higher efficacy for receptor activation than the physiological agonist. Until now, such 'superagonism' has rarely been reported for GPCRs. Iperoxo is an extremely potent muscarinic receptor agonist. We hypothesized that iperoxo is a 'superagonist'. Experimental Approach Signalling of iperoxo and newly synthesized structural analogues was compared with that of ACh at label‐free M2 muscarinic receptors applying whole cell dynamic mass redistribution, measurement of G‐protein activation, evaluation of cell surface agonist binding and computation of operational efficacies. Key Results In CHO‐hM2 cells, iperoxo significantly exceeds ACh in Gi/Gs signalling competence. In the orthosteric loss‐of‐function mutant M2‐Y1043.33A, the maximum effect of iperoxo is hardly compromised in contrast to ACh. 'Superagonism' is preserved in the physiological cellular context of MRC‐5 human lung fibroblasts. Structure–signalling relationships including iperoxo derivatives with either modified positively charged head group or altered tail suggest that 'superagonism' of iperoxo is mechanistically based on parallel activation of the receptor protein via two orthosteric interaction points. Conclusion and Implications Supraphysiological agonist efficacy at muscarinic M2 ACh receptors is demonstrated for the first time. In addition, a possible underlying molecular mechanism of GPCR 'superagonism' is provided. We suggest that iperoxo‐like orthosteric GPCR activation is a new avenue towards a novel class of receptor activators. Linked Article This article is commented on by Langmead and Christopoulos, pp. 353–356 of this issue. To view this commentary visit http://dx.doi.org/10.1111/bph.12142